KAJIAN HUKUM TERHADAP PUTUSAN MAHKAMAH AGUNG ATAS PERKARA NO.825K/PDT.SUS-PHI/2015 TENTANG PEMUTUSAN HUBUNGAN KERJA KARENA ALASAN EFISIENSI - Andika Pramana Putra; Rasji . (Jurnal Hukum Adigama, 2018)
At this time layoffs for efficiency reasons are still a polemic because there are two different interpretations caused by the provisions of Article 164 Paragraph (3) of the Manpower Law. This raises problems in Manpower so it needs to be investigated in this paper is whether in case No.825K / Pdt.Sus-PHI / 2015 has been in accordance with the efficiency criteria set by Law Number 13 Year 2003 on Manpower. The research method used in this writing is the method of normative legal research. Based on the results of the analysis that layoffs for efficient reasons is one of the reasons of the many causes of layoffs provided for in Article 164 of the Manpower Act. In the case of No.825K / Pdt.Sus-PHI / 2015, the layoffs made by PT. PG. Gorontalo Unit PG. Tolangohula, to employees of Cindra Husain is not in accordance with the provisions set forth in Article 164 paragraph (3) of the Manpower Act specifically regulating the Amount of Severance Pay as it does not take into account the Wages of Workers during the Court proceedings. This is corroborated by the Supreme Court Judge declining the appeal of the cassation and the company is considered to have committed acts contrary to the Manpower Act.